Architectural style influenced by the East Indian community - Mumbai Archive Project Team (Jio Institute, 2024)
Some houses in Kandivli village feature sloping roofs covered in terracotta tiles, extended wooden balconies, and staircases. This architectural style in Kandivli was influenced by the East Indian community, known for similar building styles in Mumbai neighbourhoods like Chuim, Kotachiwadi, and Matharpacady.